Aplikasi Theory Middle Range “The Health Promotion Model of Pender” Terhadap Faktor-Faktor yang Mempengaruhi Tingkat Kecemasan Pada Remaja Putri di Masa Pubertas: Literature Riview - Dumar, Bergita; Sri Mulyani; Ida Wahyuni; Mery Eka Yaya Fujianti (Universitas Nazhatut Thullab Al- Muafa Sampang, 2025)
Background: Anxiety is often experienced by adolescents due to various changes that occur both biologically, psychologically, and socially, which can affect their emotional state. Objective: This study aims to discuss the application of the middlerange theory